Astronomy education in geomatics - Che Awang, Mohamad Saupi; Kamarudin, Md. Nor (2007)
Traditionally, geomatics activities deal with determining precise azimuth, positioning and timing. The dependency on astronomical techniques for carrying out such practices has been well understood. However, with the availability of space-based positioning, navigation and timing (PNT) technologies especially the United States’ Global Positioning System (GPS), the Russian’s GLObal NAvigation Satellite System (GLONASS), and other Global Navigation Satellite Systems (GNSS), most of the astronomical tasks in geomatics practices have been taken over by the emerging GNSS technologies. Because of that, astronomy is seen has no longer role to play and thus should be discarded in the present geomatics curriculum. This view is misleading. In fact, astronomy has continuous role to play even in the space based era. Astronomy in geomatics education is vital for at least two reasons: first, it provides the basic knowledge of space based technologies, and second, it enhances the fundamental studies in Islamic astronomy as part of human capital development in Malaysia. This paper overviews the astronomy in geomatics education focusing the syllabus in geomatics curriculum, its learning and teaching activities at Universiti Teknologi Malaysia (UTM), Johor Bahru, Malaysia.